The Structure of Peer Feedback - Z Zainurrahman (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2021)
This article aims to propose an overview of structured peer-feedback applications. Even though peer-feedback is no longer a new thing in the world of teaching writing, until now there are still many researchers who are interested in studying it and not a few teachers are still using it. Research that has been conducted to test the effectiveness of peer-feedback and student responses to peer-feedback activities still shows different results. One thing that needs to be considered important is that differences in the results of peer-feedback use and research may result from unstructured application of peer-feedback. Experts have indicated that peer-feedback can be applied flexibly. They imply that peer-feedback activity should not be restrained in a rigid system. However, research suggests that without careful preparation, peer-feedback activity is unlikely to produce satisfactory results. In order for peer-feedback activity to be prepared, special stages in implementing peer-feedback cannot be avoided. Meanwhile, we are faced with the fact that until now there is no system that regulates the peer-feedback structure. It is for this reason that this article was written. Using literature research, this article provides a peer-feedback structure worthy of attention.